Behaviour of Wild, Non-Adult Bornean White-Bearded Gibbons (Hylobates albibarbis) in Indonesia - Cheyne, Susan; Quiroga, C. Julia; Moise, Kate L.; Mawdsley, Claire E.; Astaras, Christos; K, Abdulaziz; Cahyaningrum, Eka (HAYATI Journal of Biosciences, 2025)
Primates have an extended juvenile period associated with critical social and environmental learning. In particular, social play is positively associated with brain size in primates, indicating an important role in cognition and development. However, this behaviour has been overlooked in the Hylobatidae family. The activity patterns of eight non-adult Bornean white-bearded gibbons (Hylobates albibarbis) from four groups were studied in the Sebangau peat-swamp forest in Borneo from 2005 to 2019. We compare our findings to previous reports for adult conspecifics, report the directionality of non-adult play behaviour, and examine whether the weather impacts daily activity patterns. Feeding (39.5%), resting (27.6%) and travelling (23%) were the main activities of juveniles, while infants mostly played (42.1%) or clung to their mothers (38.3%). Non-adult groups socialised and observed their surroundings more often, and they travelled and called less often than adults. Feeding and resting frequency did not differ significantly from that of adults. Infants engaged in self-centred play twice as often as juveniles and directed most of their playing attention towards sub-adults (58%). Weather variables, previously reported to be good predictors of certain adult activities, such as singing, did not appear to affect infant and juvenile activities. Play is a critical part of primate physical and social development, and this study describes some key behaviours of young gibbons. Understanding the play behaviour of gibbons in the wild will help inform the rehabilitation of an ever-increasing number of orphaned individuals who are victims of the illegal pet trade.